Partisipasi Masyarakat dalam Ketentraman dan Ketertiban Umum di Desa Imandi, Kecamatan Dumoga Timur, Kabupaten Bolaang Mongondow - Jeane Mantiri; Cynthia Maria Siwi (Society, 2020)
This study aims to analyze and describe the public participation level and the factors supporting and inhibiting public participation in maintaining peace and order in Imandi Village. This research uses a descriptive qualitative research method. This research was located in Imandi Village, East Dumoga Subdistrict, Bolaang Mongondow Regency, North Sulawesi Province, Indonesia. The results showed that: 1) The Imandi Village community’s participation is still not well implemented. Therefore, it will be better to maintain public peace and order in the village if it starts from individuals as small community units. It allows the realization of solidarity, which will significantly affect group members or community members in public peace and order implementation. 2) Efforts to motivate people to participate through Mapalus (mutual assistance activities) need leaders who can be role models. Village community leaders can be the key motivator in mutual assistance activities, but the government’s participation is required. (3) The village government and its apparatus must continue to managing and fostering community members, especially in multicultural communities, to prevent the disruption of public peace and order.